Hábitos alimentarios durante la gestación materna de mujeres kichwas de la comunidad de Ashambuela del Cantón Cotacachi. (Caso de estudio comparativo por edad entre dos grupos de mujeres)) - Tambaco, Johanna E. (2020)
This research aimed to analyze eating habits during the maternal gestation of two intergenerational kichwas women's groups from the Ashambuela community of Cantón Cotacachi through a comparative study from a ethnographic perspective. The work was mainly based on a qualitative method that allowed the application and collection of testimonies through interviews with the research interest group: knowing what kind of meals they eat, ingredients, condiments and beverages that they consume during the stage of pregnancy as well as the spaces of the kitchen, the people who prepare the food and those that are present during it. In this way, other related groups were also detached, such as midwives of the different communities of The Cantón Cotacachi, and the medical staff of the Asdrúbal la Torre Health Center: gynecologist, obstetrician and nutritionist to learn more about the type work and recommendations they make about eating habits from "what should and shouldn't they eat" pregnant women and what physiological changes a woman tends to have at every stage of pregnancy. All of these groups were a key part of the development of research. .